2013
DOI: 10.1128/jvi.01678-13
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DNA Binding and Transactivation Domains Affect the Dynamics of Parvovirus NS1 Protein

Abstract: The multifunctional replication protein of autonomous parvoviruses, NS1, is vital for viral genome replication and for the control of viral protein production. Two DNA-interacting domains of NS1, the N-terminal and helicase domains, are necessary for these functions. In addition, the N and C termini of NS1 are required for activation of viral promoter P38. By comparison with the structural and biochemical data from other parvoviruses, we identified potential DNA-interacting amino acid residues from canine parv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…There are also limited studies on the NS1 protein, based only on evaluations of its functions [66,67,68] and on the potential location of its functional domains [10,22,23]. Changes in specific residues of NS1 CPV sequence [27] or affecting functional domains in others Carnivore protoparvovirus 1 such as mink enteritis parvovirus [69] were hypothesized as potentially affecting the functions of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also limited studies on the NS1 protein, based only on evaluations of its functions [66,67,68] and on the potential location of its functional domains [10,22,23]. Changes in specific residues of NS1 CPV sequence [27] or affecting functional domains in others Carnivore protoparvovirus 1 such as mink enteritis parvovirus [69] were hypothesized as potentially affecting the functions of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Among encoded structural proteins, VP2 is the major capsid protein, represents the main determinant of host range, and is subject to antibody-mediated selection [20,21]. On the other hand, the nonstructural proteins NS1 and NS2 are essential for viral replication, DNA packaging, cytotoxicity, and pathogenicity [22,23,24]. Due to the involvement of the VP2 capsid protein in host switch and due to its fast evolutionary rate, most studies on CPV and FPLV focused their attention on the VP2 gene and on the structural analysis of the encoded protein.…”
Section: Introductionmentioning
confidence: 99%
“…NS1 is a multifunctional nuclear phosphoprotein responsible for viral replication, cellular transcription and cell death inducing apoptosis (Gupta et al, 2016;Saxena et al, 2013). Only recently some of CPV NS1 amino acids were associated to specific functions (Niskanen et al, 2010(Niskanen et al, , 2013. In order to contribute to future studies on this gene, we provided a complete genome NS1 sequencing for a number of CPV strains.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our PLA studies revealed that CPV NS1 was located in close proximity to H3K27ac in the enlarged APAR bodies. Our earlier studies indicated that CPV NS1 has two distinct binding sites in the viral genome (53,54,57). It is tempting to speculate that NS1 is involved in the histone acetylation of viral P4 and P38 promoters by recruiting host proteins with acetyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our analysis demonstrated that H3K27ac was located in close proximity to the viral NS1 protein in the APAR bodies. This interaction likely is caused by the accumulation of NS1 on viral genomes because of its involvement in transcription and replication (52)(53)(54). NS1 of autonomous parvoviruses not only controls the viral activities but also regulates host gene expression through histone acetylation in cancer cells by recruiting innate proteins with HAT activity (55,56).…”
Section: Discussionmentioning
confidence: 99%